Pengaruh Kualitas Produk dan Harga terhadap Loyalitas Konsumen : (Studi Kasus pada Seafood Zonatri 68) - Hendri Sucipto (Jurnal Visi Manajemen, 2024)
The purpose this research is to examine the effect of product quality and price on consumer loyalalty in Seafood Zonatri 68. The method for this research is the quantitative method, to collect data by distributing questionnaires to consumers using the google form. The population of this study were 220 consumers and the samples were taken using slovin fotmula, so the sample was 70 consumers. The sampling technique was through purposive sampling method and data analysis tools using SPSS. The result of this study stated the product quality variable (X1) had a significant influence on the consumer loyalty variable (Y) with a value of 0,003<0,05 and t count 3,072>t table 1,998; the price variable (X2) has no significant effect on the consumer loyalty variable (Y) with avalue of 0,108>0,05 and t count 1,631<1,998; simultaneously the variable product qulity (X1) and price (X2) have a significant effect on the consumer loyalty variable(Y) with a value 0,000<0,05 and F count 7,693> Ftable 3,13.